О колчанных наборах скифов первой половины — середины V в. до н.э. (башневидный горизонт) / On the Formation of Scythian Quiver Sets in the first half — middle of the 5th century BCE (tower-form horizon) - Daragan M.N. (Материалы по археологии и истории античного и средневекового Причерноморья, 2020)
A series of burials was defined with identical tower-form arrowheads with the groove reaching the point, П-formed groove covering ⅔ of the arrowhead length, and small extended sleeve and size of 2—3,5 cm, and weight of 1,4—2,7 gr. Warriors, in which burials such arrowheads were found, were contemporaries. The lifetime of such arrowheads from these burials is limited to the period of the first half — no later than the third quarter of the 5th century BCE, according to their deposition in the funerary complexes. The studied series of tower-form arrowheads are solely the product of Northern Black Sea Region. Tower-form arrowheads of this time are fundamentally different from the preceding symmetrical arrowheads second half of the 6th century BCE — beginning of 5th century BCE, and arrows replacing them, forming a horizon of “cross-shaped marks” dating from the third quarter of the 5th century BCE. The appearance of series of technically and stylistically identical arrowheads on the relatively large area points to the fact that they not only were produced in the same environment, but also that there existed market-oriented craft industries. The source of supply could be seen as a single master or a single workshop or a variety of shops, but using the same templates.